O instituto da licitação como instrumento de atuação estatal na atividade econômica sob a perspectiva da teoria do paternalismo libertário - Silva, Natúcia Santos da (2024)
Public procurement is gaining increasing relevance in the national economic scenario, expanding beyond its traditional functions of selecting the most advantageous proposal to meet the needs of the Public Administration. It is transforming into a strategic mechanism that the State uses to foster economic and social development, in addition to promoting the implementation of constitutional principles and foundations. In this context, analyzing how public procurement legislation is integrates with the national Economic Order allows us to understand the role of the State not only as a regulator but as a facilitator, which enables the effective implementation of strategic public policies. The problem involving the research is to identify: which provisions of the new Bidding Law, Law No. 14,133/2021, function as state action tools that encourage good practices on the part of bidders and to what extent these devices can be framed within the theory of Libertarian Paternalism, proposed by behavioral economists Richard H. Thaler and Cass R. Sunstein, in the book “Nudge – Improving decisions about health wealth and happiness”? The hypothesis of the study says that the legislation contains provisions that, although they are conditions for participation in the bidding, are not considered repressive or restrictive norms, but rather incentives, since bidders have the free will to participate or not in the bidding. Thus, the theory of Libertarian Paternalism can be used as a justifying theory for this State action. Regarding the relevance of the research, legally, the author brings reflections on the possible trend of change in the role of the traditional Regulatory State, considering its horizontal action with the individual and with companies, in order to achieve its constitutional foundations. Academically, it is expected to contribute to the scientific discussion about the applicability of this form of action and this theory to other themes and standards. The research method used is hypothetical-deductive with a descriptive methodological approach. As for the research method for data collection, indirect observation was used, carried out through the bibliographical research technique, with national and foreign authors, being jurists, philosophers and economists of reference in the researched field, as well as in pertinent legislation. The findings confirm that the new bidding legislation incorporates principles of Libertarian Paternalism by establishing mechanisms that, although they condition participation in bidding, do not impose restrictions in a coercive manner, but encourage good practices.